Effectiveness of an oral cholera vaccine campaign to prevent clinically-significant cholera in Odisha State, India. Issue 21 (15th May 2015) - Wierzba, Thomas F.; Kar, Shantanu K.; Mogasale, Vijayalaxmi V.; Kerketta, Anna S.; You, Young Ae; Baral, Prameela; Khuntia, Hemant K.; Ali, Mohammad; Kim, Yang Hee; Rath, Shyam Bandhu; Bhattachan, Anuj; Sah, Binod
Highlights: A phase III, clinical trial conducted in Kolkata showed that Shanchol, an oral cholera vaccine, provides 65% protection against cholera over five years. To test the usefulness of this vaccine when deployed by public health department personnel using local resources, we conducted a mass vaccination campaign in a rural cholera-endemic area of India. At the end of two years, the vaccine was found to reduce cholera cases by 69%. This study supports widespread use of Shanchol by local health departments in cholera-affected areas of India and other nations. Abstract: Background: A clinical trial conducted in India suggests that the oral cholera vaccine, Shanchol, provides 65% protection over five years against clinically-significant cholera. Although the vaccine is efficacious when tested in an experimental setting, policymakers are more likely to use this vaccine after receiving evidence demonstrating protection when delivered to communities using local health department staff, cold chain equipment, and logistics. Methods: We used a test-negative, case-control design to evaluate the effectiveness of a vaccination campaign using Shanchol and validated the results using a cohort approach that addressed disparities in healthcare seeking behavior. The campaign was conducted by the local health department using existing resources in a cholera-endemic area of Puri District, Odisha State, India. All non-pregnant residents one year of age and older were offered vaccine. Over the next two years, residents seeking care for diarrhea at one of five health facilities were asked to enroll following informed consent. Cases were patients seeking treatment for laboratory-confirmed V. cholera -associated diarrhea. Controls were patients seeking treatment for V. cholerae negative diarrhea. Results: Of 51, 488 eligible residents, 31, 552 individuals received one dose and 23, 751 residents received two vaccine doses. We identified 44 V. cholerae O1-associated cases and 366 non V. cholerae diarrhea controls. The adjusted protective effectiveness for persons receiving two doses was 69.0% (95% CI: 14.5% to 88.8%), which is similar to the adjusted estimates obtained from the cohort approach. A statistical trend test suggested a single dose provided a modicum of protection (33%, test for trend, p = 0.0091). Conclusion: This vaccine was found to be as efficacious as the results reported from a clinical trial when administered to a rural population using local health personnel and resources. This study provides evidence that this vaccine should be widely deployed by public health departments in cholera endemic areas.